Pembelajaran Musik dengan Menggunakan Metode Penokohan Pada Anak Usia Dini - Sagala, Mastri Dihita; Zakarias Aria Widyatama Putra (Institut Agama Islam Negeri Madura, 2024)
It is very important to introduce art learning from an early age because it can explore children's potential, so appropriate methods are needed to teach it. This research aims to reveal music learning using the characterization method in early childhood at Favore Music School. When applying this method, children not only listen and hear the story but also take part in acting out the character of a character. This method is found in the Little Musician class which consists of four children aged 3-4 years (toddlers). This research is classified as qualitative research by describing findings that are important to collect, organize, organize and conclude clearly. To obtain these findings, collection techniques were carried out through observation, interviews, documentation and literacy studies. The results of this research are that the characterization method used in music material in the Little Musician Class can improve musical abilities in young children. Not only skills in identifying sounds and playing musical instruments, this method can train children's self-confidence when carrying out the roles requested by the teacher. Apart from that, children become more active and socialize with friends classmates because role-playing activities require children to interact with their environment.